2009
DOI: 10.1142/s0219649209002361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technological Innovation Capabilities on the Market Value of Firms

Abstract: Abstract. In the era of globalisation and with the advent of knowledge economies, organisational innovation has assumed a critical role in enhancing economic performance of¯rms. Proponents of the Resource Based View of the¯rm and its more recent extensions such as the Knowledge Based View and Dynamic Capabilities Theory have suggested that generation, di®usion and application of organisational knowledge could be the source of sustained competitive advantage and superior performance of¯rms. While there is near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The knowledge-based theory of the¯rm (Grant, 1996) extends the RBV to posit that knowledge is the¯rm's most valuable, rare, and inimitable resource, and hence, the most strategic. Firms exist to create knowledge and this knowledge explains sustained competitive advantage between¯rms (Annavarjula and Mohan, 2009). Firms selling products ranging from cement to consulting services understand this and are trying to become more knowledge-based (Zack, 2003).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The knowledge-based theory of the¯rm (Grant, 1996) extends the RBV to posit that knowledge is the¯rm's most valuable, rare, and inimitable resource, and hence, the most strategic. Firms exist to create knowledge and this knowledge explains sustained competitive advantage between¯rms (Annavarjula and Mohan, 2009). Firms selling products ranging from cement to consulting services understand this and are trying to become more knowledge-based (Zack, 2003).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Sorescu and Spanjol (2008) concluded that breakthrough innovation is associated with increases both in normal profits and economic rents, and that, on average, each breakthrough innovation in the sample is associated with an increase in firm value. Breakthrough innovation is also associated with increases in the risk of the innovating firm, but this higher risk is offset by above-normal stock returns.The study by Annavarjula et al (2008) found that R&D spending positively impacts the fi rm value both immediately and over time. Belenzon and Patacconi (2012) used data from more than 33,000 mergers and acquisitions deals between 1985 and 2007, and distinguish between American (USPTO) and European (EPO) patents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Damanpour et al (2009) indicated that a firm's ability to acquire and exploit external knowledge is often critical to achieving and sustaining a competitive advantage. Annavarjula and Mohan (2009) era of globalisation and with the advent of knowledge economies, organisa tional innovation has assumed a critical role in enhancing economic performance of firms. Fariborz et al (2009) showed that the impact of innovation on organizational performance depends on compositions of innovation types over time.…”
Section: Effects Of New Product Development On the Profitability Of Tmentioning
confidence: 99%